Discovering Modern C++ : An Intensive Course for Scientists, Engineers, and Programmers - Gottschling, Peter, ....- (Boston : Addison Wesley, 2022)
Discovering Modern C++, Second Edition, will help you master valuable skills for programming with C++ at nearly every level, from "close to the hardware" to high-level abstractions. Updated for C++17 and C++ 20, this intensive introduction teaches C++ using realistic examples from diverse technical problem domains. Drawing on extensive experience teaching C++ to physicists, mathematicians, engineers, and students, Peter Gottschling guides you smoothly to sophisticated approaches based on advanced features. Whatever your programming experience, you'll rapidly master increasingly powerful features, from lambdas to expression and variadic templates. Gottschling also shows you how to apply C++'s libraries: both the Standard Template Library (STL) and scientific libraries for arithmetic, linear algebra, differential equations, and graphs. Step by step, you'll learn to write clear and expressive code using object orientation, generics, metaprogramming, and procedural techniques, and master all the abstractions you need to write high-quality, well-performing software.
Keywords: C++.; Programmeren